Exploring spontaneous interactions between people with profound intellectual and multiple disabilities and their peers. Issue 3 (3rd July 2019) - Kamstra, A.; van der Putten, A. A. J.; Maes, B.; Vlaskamp, C.
ABSTRACT: Background: Peers living in the same group form important interaction partners for people with profound intellectual and multiple disabilities (PIMD). Given the severity of their disabilities, direct support persons (DSPs) play a significant role in facilitating interactions between these peers. This study explores the spontaneous interactions between persons with PIMD and the possibilities provided by DSPs related to physical positioning. Method: Observational data were obtained from 14 people with PIMD for three consecutive hours in a non-controlled situation. Results: Of all 213 observed interactions, 5.1% were with peers, 73.4% with DSPs, 14.9% with the observer, and 6.5% with others. In 61.3% of the observed timeframes, the participants with PIMD were positioned in a way that made it impossible to touch or/and to look at a peer. Conclusion: Generally, the observed positioning of the participants made contacts between peers nearly impossible. DSPs should create optimal conditions for interaction between peers.